SUPPLY CHAIN ARCHITECTURE RECONFIGURATION: BUSINESS CONTINUITY MANAGEMENT (BCM) INTEGRATION AS A DETERMINANT OF OPERATIONAL RESILIENCE - David Ramadian; Niken Dwi Utari; Pramiantoro Sumaryono; Rio Stefanus Guntoro; Rakesh Sitepu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The escalating complexity of global supply chain networks has amplified corporate exposure to systemic disruptions, rendering traditional efficiency-centric paradigms such as Just-in-Time (JIT) increasingly vulnerable. This study interrogates the strategic imperative of integrating Business Continuity Management (BCM) within supply chain architecture to enhance organizational resilience. Utilizing a qualitative descriptive approach through a comprehensive literature review, this research delineates the transition from reactive risk mitigation to proactive adaptability. The analysis highlights that embedding ISO 22301 standards, executing rigorous Business Impact Analysis (BIA), and adopting supplier diversification strategies are critical determinants for sustaining operational continuity. The findings suggest that resilience is not merely a defensive mechanism but a strategic capability that requires the decoupling of supply chain dependencies through multi-tier visibility.